Human rights in South Africa’s foreign policy under President Cyril Ramaphosa (2019-2024) : a case study of Ukraine - Mutton, Jan F. (University of Pretoria, 2025)
Mini Dissertation (MPhil (Multi-Disciplinary Human Rights)--University of Pretoria, 2024.